Understanding factors underlying actual consumption of organic food: The moderating effect of future orientation - Brahim Chekima; Khadidja Chekima; Khalifa Chekima (Elsevier Ltd, 2019)
The majority of past studies focused on investigating the motivational factors to purchase organic food as a proxy to foster organic food consumption. However, the preceding studies’ foci do not embrace the consumption itself where purchasing may come secondary to consumption decisions. Consumption reflects high involvement with the product; and the barriers and motivations are as real as the product itself, which makes it an ideal moment to examine the motivation. The research model was analyzed using the Partial Least Square Structural Equation Modeling technique. Results show that product-specific attitude (PSA), willingness to pay (WTP) and perceived availability (PA) had a significant positive influence on individuals’ organic food consumption (OFC), while environmental attitude (EA) and subjective norms (SN) were not significantly related. The moderating role of future orientation (FO) between PSA, EA, WTP and OFC were examined and found to be significant except for EA. The result suggests that PSA and WTP are stronger and higher respectively when future orientation is high. The research provides a significant insight and better understanding of organic food actual consumption behavior and adds a new momentum to the growing literature. Discussions and implications of these findings are further discussed.